Realization of Deixis Theory by Major Characters of Jumanji: The Next Level Movie - Sari, Risye Novita; Kurniawan, Ildi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study investigates the types of deixis used by major characters in Jumanji: The Next Level movie script, based on Levinson's (1983) theory. Descriptive quantitative methods were used in this research. Data was collected using an observation checklist and analyzed using statistical formulae. Results showed that all deixis suggested by Levinson were used: Person deixis (66.2%), time deixis (3.76%), place deixis (8.20%), discourse deixis (15.84%), and social deixis (6.15%). it can be concluded that the major characters in the movie often use persona deixis and discourse deixis.